2023
DOI: 10.1029/2023ja031409
|View full text |Cite
|
Sign up to set email alerts
|

Imprint of Storm Enhanced Density in Ground‐Based OI 630.0 nm Dayglow Measurements

Kshitiz Upadhyay,
Duggirala Pallamraju,
Supriya Chakrabarti

Abstract: The mid‐latitude upper atmosphere is directly affected by the inner magnetosphere through the interactions at the closed geomagnetic field line boundary. Several space weather phenomena associated with magnetospheric‐plasmaspheric exchanges can be mapped to mid‐latitudes. One such phenomena that occurs over mid‐latitudes during geomagnetic storms is the storm enhanced density (SED). So far, storm time ionospheric features have been studied primarily using radar, GPS and in‐situ measurements. We present high sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…WEM predictions have been shown to match well with the HIRISE measured OI 630.0 nm dayglow during geomagnetically quiet days (D. Pallamraju et al, 2020, Shepherd & Cho, 2021. Upadhyay et al (2023) showed that by applying the scaling factor between HIRISE data and WEM predictions obtained during geomagnetically quiet days, the dayglow brightness values can be obtained during geomagnetic disturbances. The same approach has been applied in this study as well.…”
Section: Model Emissionsmentioning
confidence: 64%
See 3 more Smart Citations
“…WEM predictions have been shown to match well with the HIRISE measured OI 630.0 nm dayglow during geomagnetically quiet days (D. Pallamraju et al, 2020, Shepherd & Cho, 2021. Upadhyay et al (2023) showed that by applying the scaling factor between HIRISE data and WEM predictions obtained during geomagnetically quiet days, the dayglow brightness values can be obtained during geomagnetic disturbances. The same approach has been applied in this study as well.…”
Section: Model Emissionsmentioning
confidence: 64%
“…Also, positive and negative ionospheric storms can alter the ionospheric electron densities from their mean quiet time behavior at a given latitude. Therefore, in several earlier studies, small time scale variations in Ne during geomagnetic disturbances have been shown to affect the 630.0 nm dayglow intensity variability at all latitudes (e.g., Pallamraju & Chakrabarti, 2005; D. Pallamraju et al., 1996, 2001, 2010; Upadhyay et al., 2023). Temporal variations in the dayglow emissions can also occur through the photoelectron impact mechanism on occasions, such as, occurrence of solar flares (e.g., Das et al., 2010; Sumod et al., 2014).…”
Section: Observation and Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, small time-scale temporal variation has been shown to be mainly due to the DR mechanism. Thus, it has been shown in earlier studies that variations in the Flayer Ne can be readily noticed in the O( 1 D) dayglow emission intensity variability (e.g., Pallamraju et al, 2001;Upadhyay et al, 2023). Shorter duration temporal variations can also be brought out due to changes in energetic electron flux through the PEI mechanism as in the case of magnetospheric cusps (Pallamraju et al, 2004) or solar flares (Das et al, 2010).…”
Section: Observations and Resultsmentioning
confidence: 86%